Situação atual de mães cronicamente infectadas pelo tripanosoma cruzi no estado de Goiás e triagem sorológica para infecção congênita em recém-nascidos pelo teste do pezinho na região metropolitana de Goiânia - Gomes, Taynara Cristina (2016)
The congenital transmission is considered one of the main pathways of Trypanosoma cruzi infection. Retrospective studies of pregnant women population with Chagas disease (CD) allow the study of the epidemiological profile of this population which contributes to the knowledge of the congenital CD prevalence in Brazil. This study evaluated the triage of T. cruzi congenital infection in new-borns through the newborn screening aiming the precocious detection of congenital transmission as well as its retrospective analysis of the seroepidemiological profile of the infected pregnant women dwelling in Goias State in a period of three years (2013-2015). The retrospective study used the data base of the Association of Parents and Friends of Special Needs Individuals (APAE) of Goiania. The analysis showed that the prevalence of CD infected pregnant women from 0.24% to 0.17%, with a decrease throughout the years. Most of these pregnant women had ≥31 years old, which is in accordance with the success of Triatoma infestans vectorial transmission control and transfusional control programmes, improvement in dwellings and better efficacy in diagnostics and therapeutics. The prospective study used the IFI and ELISA techniques for serology and filter paper detection. A total of 967 samples of dry blood in filter paper were collected in three public health units in Goiania and Aparecida de Goiania. From these samples 19 (1.96%) which were collected in filter paper from newborns were from mothers who declared to have CD. Results showed that 8 (42%) from the 19 samples were reagent to IgG anti-T. cruzi in both technique used. Peripheral blood was collected in seven mothers and their respective children. The serum samples were analyzed and the results confirmed IgG positive serology anti-T. cruzi with rates and titulation similar between mother and their respective newborn. Also there was accordance between the serology and the filter paper results which validates this strategy in the newborn screening triage from children from chronically infected mother. This study highlights the importance of the prenatal and neonatal care that precociously identifies the T. cruzi infection and also of programmes of health education about CD to the pregnant women population.